2013
DOI: 10.1007/s00401-013-1194-6
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and oxidative stress in gliomas with IDH1 mutations

Abstract: IDH1 mutations in gliomas associate with longer survival. Prooxidant and antiproliferative effects of IDH1 mutations and its D-2-hydroxyglutarate (2-HG) product have been described in vitro, but inconsistently observed. It is also unclear whether overexpression of mutant IDH1 in wild-type cells accurately phenocopies the effects of endogenous IDH1-mutations on tumor apoptosis and autophagy. Herein we investigated the effects of 2-HG and mutant IDH1 overexpression on proliferation, apoptosis, oxidative stress, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
59
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 39 publications
6
59
0
1
Order By: Relevance
“…This is in agreement with the fact that mitochondrial inhibitors such as metformin depend on oxidative stress to induce cell death (44). Previous reports have shown that D-2HG induces cellular oxidative stress (37)(38)(39)(40), although the underlying mechanisms remained elusive thus far. Our data indicate that inhibition of IDH-mediated NADPH production capacity and aKGDH-mediated NADH production capacity by D-2HG and the resulting metabolic stress is, at least partly, responsible for this phenomenon.…”
Section: Idhsupporting
confidence: 85%
“…This is in agreement with the fact that mitochondrial inhibitors such as metformin depend on oxidative stress to induce cell death (44). Previous reports have shown that D-2HG induces cellular oxidative stress (37)(38)(39)(40), although the underlying mechanisms remained elusive thus far. Our data indicate that inhibition of IDH-mediated NADPH production capacity and aKGDH-mediated NADH production capacity by D-2HG and the resulting metabolic stress is, at least partly, responsible for this phenomenon.…”
Section: Idhsupporting
confidence: 85%
“…Cells were cultured in humidified conditions at 37°C and 5% CO 2 . Vector and R132H mutant IDH1 stable U87MG, U138MG, and LN18 cell lines were generated as previously described (25). (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTS) cell viability assays were performed as previously described (25).…”
Section: Methodsmentioning
confidence: 99%
“…SDS-PAGE and Western immunoblotting were done on cell lysates as previously described (25) using the following antibodies: anti-tubulin, (Cell Signaling, 2125), anti R132H IDH1 (Dianova, DIA-H09), and anti-Par-4 (Santa Cruz, sc-1807).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 The conversion of glutamate to αKG is catalysed by glutamate dehydrogenase, which is the final step of glutaminolysis and can be inhibited by the antimalaria drug chloroquine and the antidiabetic drug metformin 20 22–24. In addition, IDH1 -mutated glioma cells show increased levels of autophagy, likely as a survival mechanism of cells to metabolic stress by catabolising proteins in order to provide substrates for energy production in stress/starvation contexts 25. Autophagy is inhibited by chloroquine26 and the anticancer properties of chloroquine may thus be selective for IDH1/2 -mutated cells because it inhibits glutaminolysis and autophagy on which the cells are dependent.…”
Section: Introductionmentioning
confidence: 99%